1969
DOI: 10.1063/1.1683820
|View full text |Cite
|
Sign up to set email alerts
|

Simple, High Intensity Short Pulse Flashlamps

Abstract: Various flashlamps were constructed using quartz envelopes and simple wire electrodes. The lamps were continuously evacuated to minimize explosive failures. Energies in the 10 to 1000 J range were discharged from low inductance capacitors through a triggered spark gap to the lamps. The lamp discharges occurred primarily in vapors ablated from the quartz envelopes and produced intense light pulses of 1 to 10 μsec duration with submicrosecond risetimes. Lamp explosion energies and peak light outputs were empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…We found that the rare gas gave more light output when a small amount of an impurity gas like nitrogen or CO 2 was present . The gas-fill pressures for figure 4 are 1 atm except for the ablating wall lamp which is discussed by Ferrar [4] . From figure 4 we see that xenon has about 13 per cent High power dye laser 877 more peak light power and over 50 per cent more light energy output than argon .…”
Section: Flashlamp Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…We found that the rare gas gave more light output when a small amount of an impurity gas like nitrogen or CO 2 was present . The gas-fill pressures for figure 4 are 1 atm except for the ablating wall lamp which is discussed by Ferrar [4] . From figure 4 we see that xenon has about 13 per cent High power dye laser 877 more peak light power and over 50 per cent more light energy output than argon .…”
Section: Flashlamp Characteristicsmentioning
confidence: 98%
“…The flashlamp was connected to a gas filling-station, and optical power was measured with different gas fills . Figure 4 shows a comparison of the light intensity from three different gas-fills and an ablating wall flashlamp [4] . We found that the rare gas gave more light output when a small amount of an impurity gas like nitrogen or CO 2 was present .…”
Section: Flashlamp Characteristicsmentioning
confidence: 99%
“…If wavelength dependence is of little importance and if reabsorption effects can be neglected, equation 9 may be replaced by g "" NW~rB/c (10) using for B either the peak or an average value. That means the gain G increases exponentially with pump power, which has been proved experimentally [2].…”
Section: Small Signal Gainmentioning
confidence: 99%
“…For this experiment a glass dye cell of 2 cm diameter was employed, pumped by four wall-ablating lamps [ 10] giving good uniform illumination of the cell. The radiation spectrum of these lamps is approximately that of a 30000 K black body.…”
Section: Essmentioning
confidence: 99%